2013
DOI: 10.1111/jpg.12569
|View full text |Cite
|
Sign up to set email alerts
|

3d Basin Modelling in the Central Persian Gulf, Offshore Iran

Abstract: In the Central Persian Gulf, super‐giant natural gas accumulations in Permo‐Triassic reservoirs are assumed to be derived from “hot shale” source rocks in the lower Llandoverian (base‐Silurian) Sarchahan Formation, whereas oil in Mesozoic reservoirs is derived from Mesozoic source rocks. A 3D basin model has been established for a study area located in the Iranian part of the Central Persian Gulf in order to help understand the petroleum systems there. Sensitivity analyses considered different heat flow scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In this study, bottomhole temperature and vitrinite reflectance data were used for the temperature and maturity calibrations, respectively. Recently, heat flow values in the range of 60-68 mW/m 2 were shown to be in accordance with the vitrinite reflectance measurements in the central Persian Gulf (Mohsenian et al 2014). The easy %R o kinetic model of Sweeney and Burnham (1990) was applied to calculate the thermal maturity levels of the studied formations.…”
Section: Methodssupporting
confidence: 74%
“…In this study, bottomhole temperature and vitrinite reflectance data were used for the temperature and maturity calibrations, respectively. Recently, heat flow values in the range of 60-68 mW/m 2 were shown to be in accordance with the vitrinite reflectance measurements in the central Persian Gulf (Mohsenian et al 2014). The easy %R o kinetic model of Sweeney and Burnham (1990) was applied to calculate the thermal maturity levels of the studied formations.…”
Section: Methodssupporting
confidence: 74%
“…The thermal history at the sediment-water surface (SWIT) over geological times can be obtained by using the modules from PetroMod software [55]. SWIT was assigned by global unified SWIT-Time template from PetroMod software incorporated with regional geography position (North latitude 45°) in Xujiaweizi Fault Depression of Songliao Basin.…”
Section: Geological Applicationmentioning
confidence: 99%
“…This model was a dynamic expression of the sedimentary structure and geological evolution [31]. Moreover, this model could reveal the organic maturation and petroleum-generation rules throughout various geological periods [28,[32][33][34]. After studying scholars' research on 3D basin modeling, we believe that the model accuracy can be improved by comprehensive calibration methods [31,35,36].…”
Section: Introductionmentioning
confidence: 95%
“…After studying previous research on basin modeling, we found that the reservoir was defined as the default sandstone when following the common workflows [24,28,55]. We attempted to define the properties of the sandstone within the scope of the Changling Depression and distinguish among the different formations.…”
Section: Petrophysical Settingsmentioning
confidence: 99%
See 1 more Smart Citation